Q&A - Ask Doubts and Get Answers

Clear All
The detailed solution for the above-written question is we can write 125 =  and  can be written as  Now, rewriting the equation, we get .............by using     .....................Use   .........................As  .  can be cancelled out with the denominator   
The detailed solution for the above-written question is as follows we can write  So, after rewriting the equation, .................using the form     .............(By expanding we have now)

Q6. Evaluate

    (ii)   \left ( \frac{5}{8} \right )^{-7}\times \left (\frac{8}{5}\right)^{-4}

The detailed solution for the above-written question is as follows .............by using     
We have, Here a = 5 and n =-3 and m-n = 5 therefore,   By comparing from both sides we get  m+3 = 5  m= 2 

We clearly see that this is in the form of  a^{-m}=\frac{1}{a^{m}}

So, (5^{-1}\times 2^{-1})\times 6^{-1}= (\frac{1}{5}\times \frac{1}{2})\times \frac{1}{6}

                                              = \frac{1}{60}

View More
The detailed explanation for the above written question is as follows after rewriting the above equation we get,          ...........as we know that                                An alternate method, here you can use first   and after that use 
The detailed explanation for the above-written question is as follows .............. BY using these form of exponential  ......... use this                                   
The detailed explanation for the above-written question is as follows, This is the exponential form So,            .......................using this form                = 4+9+16       = 29
The detailed explanation for the above-written question is as follows Rewrite the equation       ................................. ........................                               
The detailed explanation for the above-written question is as follows, As we know that   So,  now, 
The detailed solution for the above-written question is as follows, we know the exponential forms          &          So, according to our data, here initially we use first forms and then the second one.                              
The detailed explanation for the above-written question is as follows As we know the exponential form  By using these two form we get,                             
The detailed solution for the above-written question is as follows, We know the exponential formula So, 
The detailed solution for the above-written question is as follows We know the exponential formula         and     and     So, we have given  a = 1, b=2   By using above exponential law,                            
The detailed solution for the above-written question is as follows We know the exponential formula         and    So according to this  a = -4, m = 5 and n = 8                       
The detailed solution for the above-written question is as follows We know that,                       So, here     a = 1 and b = 2 and m =-5 According to the law of exponent                                  
The detailed explanation for the above-written question is as follows We know that, So, here (a = -4) and (m = 2) Then according to the law of exponent    [  negative negative = positive]
The detailed explanation for the above-written question is as follows, We know that, So,    here m  =2 and a = 3 
Exams
Articles
Questions